Plasmodium vivax merozoite surface protein 8 cloning, expression, and characterisation (2004)
Plasmodium vivax, one of the four parasite species causing malaria in humans, is the most widespread throughout the world, leading to nearly 80 million cases per year, mainly in Latin-America and Asia. An open reading frame encoding the Plasmodium falciparum merozoite surface protein 8 P. vivax homologue has been identified in the present study by screening the current data obtained from this parasite’s partially sequenced genome. This new protein contains 487 amino-acids, two epidermal growth factor like domains, hydrophobic regions at the N- and C-termini compatible with a signal peptide, and a glycosylphosphatidylinositol anchor site, respectively. This gene’s transcription and its encoded protein expression have been assessed, as well as its recognition by P. vivax-infected patients’ sera. Based on this recognition, and a previous study showing that mice immunised with the Plasmodium yoelii homologous protein were protected, we consider the PvMSP8 a good candidate to be included in a multi-stage multi-antigen P. vivax vaccine.